Applications and challenges of rhodopsin-based optogenetics in biomedicine - Zhang, Hanci; Fang, Hui; Liu, Deqiang; Zhang, Yiming; Adu-Amankwaah, Joseph; Yuan, Jinxiang; Tan, Rubin; Zhu, Jianping (Frontiers in Neuroscience, 2022)
Optogenetics is an emerging bioengineering technology that has been rapidly developed in recent years by cross-integrating optics, genetic engineering, electrophysiology, software control, and other disciplines. Since the first demonstration of the millisecond neuromodulation ability of the channelrhodopsin-2 (ChR2), the application of optogenetic technology in basic life science research has been rapidly progressed, especially in neurobiology, which has driven the development of the discipline. As the optogenetic tool protein, microbial rhodopsins have been continuously explored, modified, and optimized, with many variants becoming available, with structural characteristics and functions that are highly diversified. Their applicability has been broadened, encouraging more researchers and clinicians to utilize optogenetics technology in research. In this review, we summarize the species and variant types of the most important class of tool proteins in optogenetic techniques, the microbial rhodopsins, and review the current applications of optogenetics based on rhodopsin qualitative light in biology and other fields. We also review the challenges facing this technology, to ultimately provide an in-depth technical reference to support the application of optogenetics in translational and clinical research.